Solar cycle dependence of ion cyclotron wave frequencies. Issue 6 (18th June 2015) - Lessard, Marc R.; Lindgren, Erik A.; Engebretson, Mark J.; Weaver, Carol
Abstract: Electromagnetic ion cyclotron (EMIC) waves have been studied for decades, though remain a fundamentally important topic in heliospheric physics. The connection of EMIC waves to the scattering of energetic particles from Earth's radiation belts is one of many topics that motivate the need for a deeper understanding of characteristics and occurrence distributions of the waves. In this study, we show that EMIC wave frequencies, as observed at Halley Station in Antarctica from 2008 through 2012, increase by approximately 60% from a minimum in 2009 to the end of 2012. Assuming that these waves are excited in the vicinity of the plasmapause, the change in Kp in going from solar minimum to near solar maximum would drive increased plasmapause erosion, potentially shifting the generation region of the EMIC to lower L and resulting in the higher frequencies. A numerical estimate of the change in plasmapause location, however, implies that it is not enough to account for the shift in EMIC frequencies that are observed at Halley Station. Another possible explanation for the frequency shift, however, is that the relative density of heavier ions in the magnetosphere (that would be associated with increased solar activity) could account for the change in frequencies. In terms of effects on radiation belt dynamics, the shift to higher frequencies tends to mean that these waves will interact with less energetic electrons, although the details involved in this process are complex and depend on the specific plasma and gyrofrequencies of all populations, including electrons. In addition, the change in location of the generation region to lower L shells means that the waves will have access to higher number fluxes of resonant electrons. Finally, we show that a sunlit ionosphere can inhibit ground observations of EMIC waves with frequencies higher than ∼0.5 Hz and note that the effect likely has resulted in an underestimate of the solar‐cycle‐driven frequency changes described here. Key Points: EMIC wave frequencies are directly correlated to solar wind cycles Frequencies related to radiation belt precipitation must also have this dependence Sunlit ionosphere screens observations of wave >0.5 Hz